Pengaruh Jenis Filter Udara Pada Sistem Injeksi Terhadap Kinerja Mesin Sepeda Motor - Mochamad Riyanto Yanuar; Ilyas Hidayat; Chovin Prandya Arvinandika Putra; Dany Dwi Yulianto; Trisma Jaya Saputra (Pusat Riset dan Inovasi Nasional, 2023)
Motorcycles are automotive products that are widely used today. One of the components is injection as part of the fuel supply in the engine equipped with a filter. The filter serves to filter the air needed for the combustion process. The purpose of this study is to determine the effect of filter type on motorcycle engine performance. The study was conducted using experimental methods on Honda Beat Injection motorcycles. There are two types of air filters that will be tested, namely standard filters and racing filters. The experiment was carried out using a dyno test machine to obtain data directly according to the resulting engine speed. The speed of the engine and the rotation of the roller of the dynamometer are measured with a tachometer. The results of these calculations are presented in the form of tables and graphs and analyzed in accordance with existing theories. The results showed the type of air filter in the injection system, affecting the performance of the motorcycle engine on the power and torque produced. The difference in power and torque obtained after using the two types of filters is different due to the large difference in density of the filter layer material, which has an influence on the air sucked into the combustion chamber. The larger the pores of the filter layer, it will affect the air sucked into the combustion chamber and the size of dirt particles that can be filtered.